Boundary layer analysis for nonlinear singularly perturbed differential equations - Robert Vrabel; V. Liska; I. Mankova (Electronic Journal of Qualitative Theory of Differential Equations, 2011)
This paper focuses on the boundary layer phenomenon arising in the study of singularly perturbed differential equations. Our tools include the method of lower and upper solutions combined with analysis of the integral equation associated with the class of nonlinear equations under consideration.